NECAB2 is an endosomal protein important for striatal function - Bueno, Diones; Dey, Partha Narayan; Schacht, Teresa; Wolf, Christina; Wüllner, Verena; Morpurgo, Elena; Rojas-Charry, Liliana; Sessinghaus, Lena; Leukel, Petra; Sommer, Clemens; Radyushkin, Konstantin; Florin, Luise; et al. (Free radical biology and medicine, 2023)
Synaptic signaling depends on ATP generated by mitochondria. Dysfunctional mitochondria shift the redox balance towards a more oxidative environment. Due to extensive connectivity, the striatum is especially vulnerable to mitochondrial dysfunction. We found that neuronal calcium-binding protein 2 (NECAB2) plays a role in striatal function and mitochondrial homeostasis. NECAB2 is a predominantly endosomal striatal protein which partially colocalizes with mitochondria. This colocalization is enhanced by mild oxidative stress. Global knockout of Necab2 in the mouse results in increased superoxide levels, increased DNA oxidation and reduced levels of the antioxidant glutathione which correlates with an altered mitochondrial shape and function. Striatal mitochondria from Necab2 knockout mice are more abundant and smaller and characterized by a reduced spare capacity suggestive of intrinsic uncoupling respectively mitochondrial dysfunction. In line with this, we also found an altered stress-induced interaction of endosomes with mitochondria in Necab2 knockout striatal cultures. The predominance of dysfunctional mitochondria and the pro-oxidative redox milieu correlates with a loss of striatal synapses and behavioral changes characteristic of striatal dysfunction like reduced motivation and altered sensory gating. Together this suggests an involvement of NECAB2 in an endosomal pathway of mitochondrial stress response important for striatal function.